Association between sociodemographic factors and alcohol consumption in rural women - Daine Ferreira Brazil do Nascimento; Georgiane Silva Mota; Bianca Beatriz Santos de Souza; Priscilla Nunes Porto; Carla Tatiane Oliveira Silva; Cláudia Geovana da Silva Pires; Jeane Freitas de Oliveira (Universidade Federal do Ceará, 2020)
Objective: to describe the association between sociodemographic factors and alcohol consumption in women from a rural community. Methods: a cross-sectional study conducted with 259 women from a rural community. For data collection, a structured form and the Alcohol Use Disorders Identification Test were used. For analysis, chi-square and/or Fisher's Exact tests were used, with a 95% confidence interval. Results: there was a statistically significant association between alcoholic consumption by the women investigated and age and zone I (p=0.043), income and zone I (p=0.081), and income and zone IV (p=0.049). Conclusion: participants with lower income consumed alcoholic beverages excessively.